Successful enucleation of a cystic nephroma in an infant: A case report - Masahiro Hatanaka; Junko Fujino; Hisashi Kanda; Kenta Kikuchi; Mariko Hasegawa; Akihiro Igarashi; Takashi Tuchioka; Kan Suzuki; kazuyuki Kojima (Elsevier, 2023)
Introduction: Pediatric cystic nephroma (PCN) is a rare benign renal neoplasm. The current treatment is a nephrectomy. We report a case of successful enucleation for a giant PCN in an infant. Case presentation: A 10-month-old female was admitted to our department due to a left upper quadrant bulge. Physical examination was unremarkable. Urinalysis showed moderate white blood cells in the sediment. Tumor markers and other general blood tests showed no abnormalities. Ultrasonography showed an enlarged left kidney with a 6 × 5 cm multiseptated cystic mass. Computed tomography revealed a multiloculated homogeneous cystic mass in the left kidney without calcifications or solid components. Magnetic resonance imaging showed a hyperintense multicystic mass. She was diagnosed with pediatric cystic nephroma based on the imaging and clinical features. The initial decision was to follow her up and only intervene if symptoms appeared. Three months later she developed abdominal distention and loss of appetite, so we decided to remove the mass. Due to its benign nature, we opted for an enucleation rather than a nephrectomy. The mass size was 90 × 85 × 70 mm. We encountered significant bleeding during the dissection but were eventually able to save the normal renal parenchyma safely. The pathology confirmed a PCN. At two years of follow up there has been no recurrence and the left kidney remains normal. Conclusion: PCN is a benign cystic lesion of the kidney that can potentially be managed by enucleation rather than nephrectomy.